The Study of Cognitive and Employability Diagnosis Factors for Supporting Role-Play Learning with Workshop Teaching Model in the Employability Diagnosis System - Jiangxia, Luo; Sriarunrasmee, Jaemjan; Chantanarungpak, Kanokphon (ASEAN Journal of Education, 2024)
This study was a part of the ongoing research project developing a role-play learning with workshop teaching model using an Employability Diagnostic System to improve the employability of Chinese college students. Employment ability is a social issue that China currently attaches great importance to and a problem that local government departments and universities attach great importance. According to the survey results, students are presently aware of employment ability diagnosis. This research proposes two objectives: 1) To synthesis the factors of Social Cognitive and Employability Diagnosis. 2) To study the correlation of the Social Cognitive factors and Employability Diagnosis. This study used quantitative research methods to explore the impact of various factors in Social Cognitive Career development theory on students’ Employability Diagnosis to support the onstruction of role-play learning and workshop teaching model based on Employability Diagnosis System. The study included a sample of a hundred students selected by using Simple Random Sampling and Purposive Sampling methods. The research instruments was a survey questionnaire. The results indicated that the Social Cognitive Career theory included five factors 1) Personal variable 2) Environmental variable 3) Learning experience 4) Human capital 5) Goal identification. The diagnosis of Employability had five aspects: 1) Job search motivation, 2) Job opportunity exploration, 3) Job performance, 4) Job search efficacy and 5) Monitoring and regulation. Furthermore, it was found that the five factors of Social Cognitive Career theory can have a positive correlation on the five aspects of students’ Employability Diagnose is in every aspect, with a significant >.05, indicating that Social Cognitive and Employability Diagnosis factors could support and promote the development of role-play learning with workshop teaching model based on Employability Diagnosis System to enhance students’ employability skills.